The forgotten road - Evans, Richard Paul (New York, NY : Simon & Schuster, 2018)
"The second novel in the New York Times bestselling trilogy from Richard Paul Evans about a man on an inspirational pilgrimage across Route 66 to find his way back to himself"--
Escaping death from a plane crash has brought Charles James some clarity: the last time he was happy was when he was married to his ex-wife Monica. Now he's walking the length of Route 66, in hopes of convincing Monica to give him another shot. As he meets people along the road who will change his perspective on the world, will his transformation be enough to earn redemption?
Sequel to: The broken road.
Keywords: Life change events -- Fiction; Pilgrims and pilgrimages -- Fiction; Divorced people -- Fiction; Celebrities -- Fiction; FICTION -- Christian -- General; FICTION -- Romance -- General; FICTION -- Romance -- Contemporary; Life change events -- Fiction; United States Highway 66 -- Fiction; Christian fiction; Road fiction; Psychological fiction; Road fiction; Romance fiction; Religious fiction; Novels; Religious fiction; Psychological fiction; Christian fiction; Romance fiction; Road fiction